A função social das transnacionais e a efetivação dos direitos humanos na era da globalização - Silva, Isis de Almeida (2019)
The current conjecture of transnationals in relation to the function they perform in a particular place goes far beyond its purely economic aspect. With the expansion of the phenomenon of globalization, as well as the reconfiguration of human concerns - which are now more humanitarian and more concerned with the sustainability of relations - these companies begin a joint process with society aiming at achievements in different spheres. In order to understand the process of transformation of the companies that were once pure and only instrumental machines of a capitalism considered as "savage" for companies based on their social responsibilities that leave this economic area and incorporate the social character, we have made a brief approach to the history of fundamental rights since the French Revolution and then with a greater focus on the twentieth century and on the events that influenced this change. The narrative of events such as the French Revolution, the Crisis of 1929 and the great wars are necessary to establish a historical context sufficiently capable of allowing us to understand at what moment globalization, as we understand it today, has expanded. After the historical contextualization, a more in-depth study of the global and national roots of globalization is described in an analytical way, allowing us to consider the effects of such phenomenon on the transnational scenario and its restructuring. In the end, the study of this strictly economic reformulation reflects in a new way of presenting itself in the international scope of companies and addresses social responsibility as a path to a full and humanized development.